2020
DOI: 10.1002/adfm.202002761
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis‐Enabled Construction of Silica Nanochannels Crossing Living Cell Membrane for Transmembrane Drug Transport

Abstract: Artificial transmembrane channel (ATC) analogs are developed for overcoming biological membrane barriers and realizing transmembrane drug delivery, which are mostly studied within artificial lipid bilayers and thus lacked enough stability in practical applications on living cells. Here, natural endocytosis of silica‐based 1D nanomaterials (nanowires) with an ultrahigh aspect ratio is investigated. Enlightened by partially endocytosed ultralong silica nanowires, ATC that can penetrate living cell membranes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…We previously demonstrated endocytosisenabled construction of transmembrane channels by using nanosized silica tubes. 6 Hereby, microsized silica tubes were cocultured with living HeLa cells to build the artificial transmembrane channels through endocytosis. It was found that the cells could hardly internalize SMT-2, probably due to the larger size of tubes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated endocytosisenabled construction of transmembrane channels by using nanosized silica tubes. 6 Hereby, microsized silica tubes were cocultured with living HeLa cells to build the artificial transmembrane channels through endocytosis. It was found that the cells could hardly internalize SMT-2, probably due to the larger size of tubes.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several kinds of transmembrane channels have been built by partially “inserting” peptide, , carbon, silica or supramolecular nanotubes , into cell membranes. Similar to the biological counterparts, these artificial channels mainly take charge of the substance exchange between the extracellular and intracellular ends, including water molecules, , protons, ionic species, , drug molecules, and even genes .…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional nanomaterials have been developed and widely used in a variety of biological applications, especially in precise tumor imaging and therapy, , showing great potential for accurate diagnosis and treatment of cancer . However, the complex tumor microenvironment displays an uneven distribution of a vascular network, cell membrane barrier, high interstitial pressure, and dense tumor tissue among other factors . These hinder the penetration of passive nanomaterials into deeper tumor tissues, resulting in uneven distribution and less enrichment of nanomaterials in the tumor .…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the complex tumor microenvironment displays an uneven distribution of a vascular network, cell membrane barrier, high interstitial pressure, and dense tumor tissue among other factors. 4 These hinder the penetration of passive nanomaterials into deeper tumor tissues, resulting in uneven distribution and less enrichment of nanomaterials in the tumor. 5 Recent studies showed that the passive accumulation dose of nanoparticles in tumor tissue is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Thus, developing more reliable and promising systems for RA treatment is highly urgent but challenging. Recently, it was found that macrophage-derived exosomes featuring good histocompatibility and low immunogenicity can be homed or targeted to inflammatory tissues or cells, 22 and they have been developed as therapeutic agents in many inflammatory or injury models, [23][24][25] for example significantly attenuating the severity of dextran sulfate sodium-induced colitis in mice, 24 attenuating thermal hyperalgesia in a murine model of inflammatory pain, 25 and activating the c-Jun/AP-1 signaling pathway in vascular smooth muscle cell dedifferentiation and vascular tissue repair processes. 26 However, the insufficient anti-inflammatory abilities and intrinsic off-target effects of these exosomes often result in unsatisfactory treatment effects, which remains a challenge in the treatment of RA or other inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%